Patterns of Distance Learning during Pandemic: Changes, Adaptation, and The Wisdom - Ruhaena, Lisnawati; Raihana, Permata Ashfi; Qatrunnada, Rizqi Zulfa (Universitas Muhammadiyah Surakarta, 2025)
The COVID-19 pandemic has challenged the ability to create new adaptive behavior in education. This research aim to understand about what kinds of changes and adaptations were required, also what wisdom could be learnt. The research approach was qualitative research, which was a case study. The participants were parents of students engaged in distance learning and selected by purposive random sampling. An open-ended questionnaire was used to collect data from 174 respondents, after whom 141 completed the behavior checklist and 8 of them were chosen to be interviewed. The data collected was then subjected to content analysis, to categorise themes and find the patterns of change, adaptation, and wisdom. The results showed the pattern of change that distance learning was perceived by parents as overwhelming, and children find it difficult and boring. The pattern of adaptations showed that parents were managing emotions, time, work, and online facilities. The children managed to adapt to boredom and the temptation to play games. The pattern of wisdom obtained was that parents had learnt how to use a gadget, the online application, and the internet. They managed keeping health by applying health protocol, and also, they had benefit of closer relationship with their children.